Strengthening Students with Ulul Albab Character through Islamic Education during the Covid-19 Pandemic (A Case Study at UIN Sunan Gunung Djati Bandung) - Sadiah, Dewi (Didaktika Religia, 2022)
Lecturers are still responsible for transferring their knowledge and trying to form good character in students even though learning is carried out online during the COVID-19 pandemic. This article aims to describe lecturers' efforts during online learning to form students with ulul albab characters, namely having good morals, achievement, scientific writings, intelligence, and dignity. This research is qualitative because data mining is done through observation, learning documentation, and interviews. After the data is collected, the analysis is done by reducing, presenting, concluding, and verifying the data. The research was conducted at UIN Sunan Gunung Djati Bandung, with the student ulul albab character as the main study. The results showed that lecturers in providing the learning process to students during the covid-19 pandemic used an exemplary approach, mauidhah hasanah, attention, affection, riyadhah, assignments, discussions/questions, and answers, and provided solutions. The lecturers do not let their students run wild with their character and achievements. They continue to evaluate students' both, evaluation of attitudes and achievements. The strengthening of these lecturers was able to maintain the excellent character of students and their achievements in the mid-semester and final exams. Changes in students' thinking can also increase, proven when they make thesis proposals. Apparently, during the past three semesters of online learning, students' understanding of the material and how to write a thesis proposal remained excellent and creative.